Microeconometric decompositions of aggregate variables: an application to labor informality in Argentina - Gasparini, Leonardo Carlos (2001)
This paper illustrates the use of microeconometric decomposition techniques to characterize changes in aggregate variables. In particular, I study the effect of changes in the employment structure on the labor informality rate for salaried workers in the Greater Buenos Aires area. To that aim I compute the difference between the informality rate at moment t´ and the rate that results from combining the population at moment t with the parameters estimated at moment t´ that link observable individual characteristics to the informality decision. The paper concludes that the deep change of the employment structure in Argentina during the 1980s and the 1990s has had a significant but minor effect on the labor informality rate.